The effect of economic freedom, economic complexity and population growth rate on per capita income - Crisnina Handayani; Marselina Marselina; Arvina Ratih (Goodwood Publishing, 2025)
Purpose: This study investigates the effects of economic freedom, economic complexity, and population growth on per capita income across different groups of countries classified by income level, namely, high-, upper-middle-, lower-middle-, and low-income countries. Methodology: This study applies panel data regression using a cross-sectional dataset covering 102 countries. Per capita income is employed as the dependent variable, while the independent variables consist of indicators of economic freedom, complexity, and population growth. Separate analyses were conducted for each income group to identify heterogeneous impacts. Results: The findings revealed diverse effects across income levels. In high-income countries, only trade freedom significantly and positively influences the per-capita income. For upper-middle-income countries, none of the variables demonstrated significant effects. In lower-middle-income countries, monetary freedom is positively related to per capita income, whereas economic complexity is negatively related. In low-income countries, business freedom is the only factor that significantly enhances per capita income. Collectively, all independent variables significantly influenced per capita income across all income groups, with adjusted R² values ranging from 28.2% to 59.6%. Conclusions: The study concludes that the drivers of per-capita income vary across income classifications. The structural differences among country groups necessitate context-specific policy approaches rather than one-size-fits-all strategies. Limitations: The use of secondary cross-sectional data and a limited set of explanatory variables may not capture the full dynamics influencing income levels. Contribution: This research enriches the discourse on economic development by offering empirical evidence of differentiated impacts across income groups, providing valuable insights for policymakers in designing tailored economic strategies.